The influence of SMEs employees' intention towards innovative behaviour - Yusof, Rosmelisa; Ng, Siew Imm; Ho, Jo Ann; Abd Rahman, Azmawani (Universiti Putra Malaysia Press, 2018)
Small and Medium-Sized Entrepreneurs (SMEs) need to be prepared for external challenges that are mostly beyond their control. SMEs need to improve their internal strength in terms of improving work processes. This, however, can only be effective if employees are innovatively improving their work. This study aims to look at the role of the employee's intention to engage in innovative behaviour based on the Theory of Planned Behaviour (TPB). The research employs the predictors of attitude, subjective norm and perceived behavioural control to affect employee's intention to engage in innovative behaviour. This study also investigates the relationship between intention and engagement in innovative behaviour. A sample of 201 SME employees working in Electrical and Electronic (E & E) SMEs in Malaysia took part in the survey assessment. The results indicate that the three antecedents of attitude, subjective norm and perceived behavioural control affect employee's intention and innovative behaviour. This study provides an understanding of employee intention and innovative behavior that serves as guidance for managers of SMEs and researchers to enhance and capitalise on the capacity of innovative employees.